Iam candidatus est fidei, quem filiorum et nepotum credens turba circumdat - Maver, Aleš (Keria (Ljubljana), 2003)
The article deals with the development of Roman pagan religion in the last centuries of its existence, especially between the third and fifth century AD. At first it describes main characteristics of Roman paganism, such as the ancient conception of the "numen" and the Roman concentration on ritual formalism. The main part of the article explores the forces which contributed to the gradual decline of the old traditions, for example the overall crisis of the Empire in the second half of the third Christian century and the dominant henoteistic tendencies in the religious development of that time. The further important issue of the article are also the numerous attempts of pagan intelligence to save the old religion, which culminated in the unsuccesfull restoration of paganism under Emperor Julian and were finally defeated under Theodosius.
Keywords: antična zgodovina; poganstvo; religija; Rimsko cesarstvo